Evaluation of the toxicity of Virola sebifera crude extracts, fractions and isolated compounds on the nest of leaf-cutting ants - Bicalho, Keylla Utherdyany; Terezan, Ana Paula; Martins, Denise Cristina; Freitas, Taís Garcia [UNESP]; Fernandes, João Batista; Da Silva, Maria Fátima Das Graças Fernandes; Vieira, Paulo Cezar; Pagnocca, Fernando Carlos [UNESP]; Bueno, Odair Côrrea [UNESP] (Hindawi, 2012)
The phytochemical study of Virola sebifera leaves led to the isolation of three lignans: (+)-sesamin, (-)-hinokinin, and (-)-kusunokinin and three flavonoids: quercetin-3-O - L-rhamnoside, quercetin-3-O - D-glucoside, and quercetin-3-methoxy-7-O - D-glucoside by using techniques as high-speed counter-current chromatography and high-performance liquid chromatography. The crude extracts, fractions, and isolated compounds were evaluated for their insecticidal and fungicidal potential against Atta sexdens rubropilosa and its symbiotic fungus Leucoagaricus gongylophorus. The bioassay results showed a high insecticidal activity for the methanol crude extract of the leaves of V. sebifera and its n-hexane, dichloromethane and ethyl acetate fractions. The fungicidal bioassay revealed high toxicity of the lignans against L. gongylophorus. © 2012 Keylla Utherdyany Bicalho et al.
Keywords: Atta; Atta sexdens rubropilosa; Fungi; Leucoagaricus gongylophorus; Virola sebifera